Color Image Watermarking For Copyright Protection - Chua, Tiong Kin (Universiti Sains Malaysia, 2005)
Watermarking is an effective and potential method for copyright protection in digital audio, image and video data. One of the media is digital image, where it can be copied and displayed widely while still maintaining the quality. Protections to these images become more and more important. One of the simple methods is to hide the data and then get back the data by owner itself, with certain secret key. The main objective of my project is to find out which color model representation is suitable apply the digital image watermarking for copyright protection. One of the watermarking techniques in frequency domain is applied. At the same time, the robustness of the implemented algorithm to the common image processing operation, example, filtering attack, noise attack, rotation attack, and lossy JPEG compression. Some images are used in the testing. Detailed description of every resulted image and watermark is show out in this report. Quality evaluation to the images is carried out and comparison is made. The quality metrics used in this project is PSNR.